1999
DOI: 10.1021/jo990845x
|View full text |Cite
|
Sign up to set email alerts
|

A New Platinum Complex Catalyzed Reaction Involving Nucleophilic Substitution at the Central Carbon Atom of the π-Allyl Ligand

Abstract: The reaction of 2-chloro-allyl acetate with sodium ethyl acetoacetate in the presence of a platinum-(0) complex gave furan derivatives. The key feature of this new platinum-catalyzed reaction is the nucleophilic substitution at the central carbon atom of π-allyl complexes. The regioselectivity of the nucleophilic attacks (central or terminal) is dependent on the pK a of the nucleophile. In addition, a labeling experiment revealed that a rapid syn-anti isomerization of the (π-allyl) platinum complexes occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Murai et al also reported that the palladium-catalyzed reaction of 2-chloroallyl compounds provides doubly substituted products with two different nucleophiles . Although they previously discovered that the platinum catalyst gave a doubly alkylated product with the malonate anion, to the best our knowledge, there is no example of the selective formation of the doubly alkylated product by palladium catalyst without phenoxide. Furthermore, these examples of the double substitution reactions were limited to the reaction of the 2-bromo- or 2-chloroallyl compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Murai et al also reported that the palladium-catalyzed reaction of 2-chloroallyl compounds provides doubly substituted products with two different nucleophiles . Although they previously discovered that the platinum catalyst gave a doubly alkylated product with the malonate anion, to the best our knowledge, there is no example of the selective formation of the doubly alkylated product by palladium catalyst without phenoxide. Furthermore, these examples of the double substitution reactions were limited to the reaction of the 2-bromo- or 2-chloroallyl compounds.…”
mentioning
confidence: 99%
“…The reaction with diethyl malonate ( 2d ) also smoothly proceeded (entry 17), but the reaction with di- tert -butyl malonate ( 2e ) resulted in a low yield (entry 18). We also examined the reaction with ethyl acetoacetate ( 2f ), but the reaction gave furan derivatives ,, in 78% yield instead of doubly alkylated product (entry 19).…”
mentioning
confidence: 99%
“…The title compound, (I), 3-acetyl-3-benzyl-5-hydroxy-6,7dimethoxy-4-methylbenzofuran-2(3H)-one is the unexpected product of the synthesis of ethyl 2-(2,5-bis(benzyloxy)-3,4dimethoxy-6-methylphenyl)-3-oxobutanoate, an important medicinal intermediate, by the procedures reported by Kucklander et al (1988) and Kadota et al (1999). In (I) ( Fig.…”
Section: Commentmentioning
confidence: 98%
“…Platinum complexes have been used to give allylic substitution reactions where a nucleophilic attack at the central carbon is also involved. 104 The chlorinated allylic acetate 143 is converted into the heterocycle 144 in good yield by this process (Scheme 43).…”
Section: C-c Coupling Reactionsmentioning
confidence: 99%